Efektifitas Pemberian Buah Pepaya (Carica Papaya L.) terhadap Kelancaran Produksi ASI pada Ibu Menyusui di Wilayah Kerja Puskesmas Tekung - Pristia Ayu Putrianti; Yessy Nur Endah Sari; Tutik Hidayati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Exclusive breastfeeding by breastfeeding mothers plays an important role in the growth and development of babies because breast milk contains substances that are beneficial for the immune system. Papaya is one of the fruits that contain laktagogum which can increase or facilitate the production of breast milk in nursing mothers. The aim of this study was to evaluate the efficiency of feeding papaya (Carica papaya L.) to nursing women in order to facilitate the regular production of breast milk. One group pre- and post-testing was employed in this investigation. Data were gathered using questionnaires and direct observations of respondents at the Tekung Health Center's working area between July and August 2022. A total of 20 respondents made up the population, and a sample of 20 respondents was chosen using a total sampling technique. Coding, editing, and tabulating are all parts of collecting data. Then the data was analyzed by computer with the help of SPSS. The results showed that before giving papaya fruit there were 18 respondents in the category of smooth breast milk production (90%) and 2 respondents in the category of non-current milk production (10%). However, after the intervention of giving papaya fruit, all respondents were in the current category with a total of 20 respondents (100%). Statistical results using the Paired T-test showed p-value of <0.001. Because H0 is rejected and Ha is approved because the p-value is less than 0.05, eating papaya fruit can help nursing moms produce breast milk more easily.